Advantages and importance of autonomous learning in teaching english in Kazakhstan (Journal of Educational Sciences, 2021)
The article considers the advantages and importance of independent learning of a student in English lessons in the process of implementing the features of the updated content of education according to the state educational standard of the Republic of Kazakhstan. Scientific research the purpose of the work is to determine the advantages and importance of independent learning in teaching English to secondary school students by conducting a scientific experiment using empirical methods. The relevance of the study is to show an experimental analysis of the impact of the system of independent learning, which is its main tasks, on the self-regulation of students in English lessons, the rapid acquisition of a new vocabulary through effective methods, the ability to speak English fluently, the development of self-di- rected writing and reading skills of students. The main directions of the study are based on experimental analysis of Secondary School students, monitoring of students ‘ activities during the study. In addition, the educational system of Nazarbayev Intellectual Schools, which are autonomous educational organi- zations in Kazakhstan, includes features of the updated educational program. Within the framework of the studied topic, theoretical and practical studies of world scientists were considered, on the basis of which practical work was carried out in one of the secondary schools of Turkestan with the help of open- closed questions, questionnaires, and methods of interviewing high school students. The data obtained were summarized, analyzed, and cleared up. As a result, the importance of independent learning in the formation of a student as a world competitive person was determined, and recommendations were made to improve the work under study.Key words: self-learning, self-management, responsibility, smart goal, result, competitiveness.